Molecular genetic analysis of an XDR Pseudomonas aeruginosa ST664 clone carrying multiple conjugal plasmids. (4th March 2020) - Li, Zhenpeng; Cai, Zhao; Cai, Zeqiong; Zhang, Yanhong; Fu, Tongtong; Jin, Yongxin; Cheng, Zhihui; Jin, Shouguang; Wu, Weihui; Yang, Liang; Bai, Fang
Abstract: Objectives: A group of ST664 XDR Pseudomonas aeruginosa strains have been isolated from a burn clinic. Here we decipher their resistomes and likely mechanisms of resistance acquisition. Methods: The complete nucleotide sequences of representative isolates were determined, by PacBio and Illumina MiSeq sequencing, and analysed for antimicrobial resistance (AMR) genes as well as sequence variations. S1-PFGE was used to determine the sizes and numbers of plasmids harboured by the isolates. Purified plasmid DNA was further sequenced by PacBio technology, closed manually and annotated by RAST. The mobility of plasmids was determined by conjugation assays. Results: The XDR P. aeruginosa ST664 clone carries 11 AMR genes, including a bla KPC-2 gene that confers resistance to carbapenems. Most of the ST664 isolates carry three coexisting plasmids. bla KPC-2 and a cluster of three AMR genes ( aadB - cmlA1-sul1 ) are encoded on a 475 kb megaplasmid pNK546a, which codes for an IncP-3-like replication and partitioning mechanism, but has lost the conjugative transfer system. Interestingly, however, pNK546a is mobilizable and can be transferred to P. aeruginosa PAO1 with the help of a co-residing IncP-7 conjugative plasmid. The bla KPC-2 gene is carried by an IS 6100 -IS Kpn27 - bla KPC-2 -ΔIS Kpn6 -Tn 1403 mobile element, which might be brought into the ST664 clone by another co-resident IncP-1α plasmid, which is inclined to be lost. Moreover, pNK546a harbours multiple heavy metal (mercury, tellurite and silver) resistance modules. Conclusions: To the best of our knowledge, pNK546a is the first fully sequenced bla KPC-2 -carrying megaplasmid from P. aeruginosa . These results give new insights into bacterial adaptation and evolution during nosocomial infections.